United States. - Department, International Monetary Fund. Monetary and Capital Markets (IMF Staff Country Reports., 2015)
This paper discusses key findings of the Detailed Assessment of Implementation of the IOSCO (International Organization of Securities Commissions) Objectives and Principles of Securities Regulation on the United States. The United States has large, well-developed, and complex securities and derivatives markets. Postcrisis, the legal mandates of the Securities and Exchange Commission (SEC) and the Commodity Futures Trading Commission (CFTC) have significantly expanded. The level of funding of both the SEC and CFTC is a key challenge affecting their ability to deliver on their mandates in a way.